2020
DOI: 10.1007/s00253-020-11006-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a gene cluster from Armillaria gallica for the synthesis of armillyl orsellinate–type sesquiterpenoids

Abstract: Melleolides and armillyl orsellinates are protoilludene-type aryl esters that are synthesized exclusively by parasitic fungi of the globally distributed genus Armillaria (Agaricomycetes, Physalacriaceae). Several of these compounds show potent antimicrobial and cytotoxic activities, making them promising leads for the development of new antibiotics or drugs for the treatment of cancer. We recently cloned and characterized the Armillaria gallica gene Pro1 encoding protoilludene synthase, a sesquiterpene cyclase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 52 publications
(77 reference statements)
2
28
0
2
Order By: Relevance
“…Gibberellin A12 is implicated in the treatment of male infertility [ 33 ]. The ∆-6-protoilludene is a precursor for the synthesis of both melleolides and armillyl orsellinates, whose cytotoxicity reflects their ability to induce apoptosis [ 34 ]. In addition, erythrodiol is an active ingredient from the herb, Rhododendron ferrugineum , which is used in TCM.…”
Section: Resultsmentioning
confidence: 99%
“…Gibberellin A12 is implicated in the treatment of male infertility [ 33 ]. The ∆-6-protoilludene is a precursor for the synthesis of both melleolides and armillyl orsellinates, whose cytotoxicity reflects their ability to induce apoptosis [ 34 ]. In addition, erythrodiol is an active ingredient from the herb, Rhododendron ferrugineum , which is used in TCM.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the pioneering biogenesis insights were only preliminary. Until now, very few studies were reported for investigating the biosynthetic process of such structurally unique molecules. ,, Lackner and coworkers reconstituted the biosynthesis of melledonol and demonstrated that the ArmB could accept varied alcohols as substrates . Recently, Ichinose et al reported three cytochrome P450 monooxygenases CYP5344B1, CYP5348E1, and CYP5348J3 from the basidiomycete Postia placenta ATCC 44394, which facilitated the hydroxylation of Δ6-protoilludene to generate Δ6-protoilludene-3-ol or Δ6-protoilludene-5-ol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This genus has been widely applied as nutraceutical medicinal mushrooms and is considered to be a treasure for melleolide discovery. , Since the report of the first orsellinic acid-derived melleolide isolated from A. mellea decades ago, a large number of bioactive protoilludane sesquiterpene aryl esters have been characterized, and the compounds of this family have recently gained interest. ,, Armillaria is a distinctive fungal genus due to its metabolic versatility and capability to decompose a diversity of plant cell wall components as recently highlighted by Sipos et al Genome mining of the strain CPCC 401429 revealed the presence of a melleolide biosynthetic gene cluster. It carries the UDPGT coding gene melO , which is hypothesized to be of producing glycosylated molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations